Influence of different drying temperatures on the amount of essential oils and citral content in Cymbopogon citratus (DC) Stapf. - Poaceae - Buggle, V. [UNESP]; Ming, Lin Chau [UNESP]; Furtado, Edson Luiz [UNESP]; Rocha, S. F R [UNESP]; Marques, Marcia Ortiz Mayo [UNESP] (My University, 1999)
Studies were conducted to show the effect of different temperatures in the drying process on the amount and quality of essential oils of Cymbopogon citratus (DC) Stapf. Leaves were harvested in the experimental field of the Agronomical Sciences College, UNESP, Botucatu, SP, Brazil in September, 1996. Blades of the leaves were cut in small parts (about 1-1,5 cm length), dried for several days at 30°, 50°, 70° and 90°C, until establishment of the weights. In the following process a hydrodistillation, during 2.5 hours, by Clevenger apparatus, was subsidized to extract the essential oils. A higher amount of oil could clearly be collected with the lower drying temperatures, except at 30°C, affected by fungus growing. Aspergillus sp., Penicillium sp., Rhyzopus sp., Cladosporium sp., Trichoderma sp. and Alternaria sp. were observed in the leaves. The analysis of the oil by GC-MS showed the variation of citral concentration of the treatments (86,1 to 95,2%). The results proved it is worthwhile to spend more time and effort in the production process using longer times of careful drying.
Keywords: Citral; Cymbopogon citratus; Drying temperatures; Essential oils yield